Stability of steel columns stiffened by stays and multiple crossarms. (September 2018) - Li, Pengcheng; Liang, Ce; Yuan, Jun; Qiao, Ke
Abstract: A pre-stressed stayed steel column (PSSC) can effectively enhance the buckling behaviour of compression columns. In the past, researchers have primarily concentrated on examining the behaviour of PSSCs with single-bay crossarms. However, research focused on PSSCs with multiple crossarms is limited. This article aims to investigate the stability behaviour of PSSCs stiffened with multiple crossarms according to geometric analysis in conjunction with finite element (FE) studies. The results show that the critical buckling modes can be complicated due to the introduction of multiple crossarms. Critical buckling deformation similar to three half sine waves can be observed. It has also been demonstrated that interactive buckling can be ignored when determining the actual buckling strength of PSSCs stiffened by multiple crossarms, though it must be considered for PSSCs with single-bay crossarms. The effects of stay diameter and pretension in the stay have been separately investigated, and the results show that the buckling strength of a steel column can be obviously enhanced even if the pretension in stays is quite small, because the stiffness of the stays can be automatically activated by column deformation. Highlights: Formula to calculating the initial pretension is derived. The critical buckling modes can be complicated by multiple crossarms. The interactive buckling behaviour can be ignored. The stiffness of the stays can be automatically activated. The effect of increasing the crossarm length too much is adverse.